Validation of the comprehensive assessment of acceptance and commitment therapy processes for youth: The CompACT‐Y - Alex Morey; Victoria Samuel; Matthew Lewis; Marc Williams (JCPP Advances)
Abstract Background Acceptance and Commitment Therapy (ACT) is a transdiagnostic approach which aims to increase psychological flexibility. Higher psychological flexibility has been associated with reduced psychological distress, mental health symptoms and improvements in well‐being and functioning. Reviews of ACT for children and young people (CYP) indicate it shows potential as an effective treatment for a range of difficulties, however a comprehensive measure of psychological flexibility processes does not exist for CYP. Following revision of the adult Comprehensive assessment of Acceptance and Commitment Therapy Processes (CompACT), through cognitive interviewing with adolescents and consultation with ACT experts, the present study aimed to assess the factor structure and validity of the revised youth measure (the CompACT‐Y). Method The CompACT‐Y measure was administered alongside measures of ACT processes, mental health and well‐being to 334 young people across six UK schools, to assess for convergent and concurrent validity. Results Exploratory factor analysis indicated a 19‐item three‐factor structure was the most stable, with all items loading above 0.50. The CompACT‐Y correlated with measures of psychological flexibility (r = ‐0.64 – 0.66), mental health (r = −0.58 – −0.66), well‐being (r = 0.57–0.65) and behaviour (r = −0.63) as expected, indicating acceptable convergent and concurrent validity. Conclusions The CompACT‐Y appears to be a valid and reliable measure of psychological flexibility in young people. Further research is needed to replicate the findings and confirm factor structure, validity and reliability, particularly in younger adolescents and those from diverse backgrounds. The CompACT‐Y offers a promising tool to improve the methodological rigour of ACT studies in young people, and has implications for the use of ACT in clinical practice.